2021
DOI: 10.3390/biology11010015
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Distortion-Based Digital Mammograms Classification Using Depth Wise Convolutional Neural Network

Abstract: Architectural distortion is the third most suspicious appearance on a mammogram representing abnormal regions. Architectural distortion (AD) detection from mammograms is challenging due to its subtle and varying asymmetry on breast mass and small size. Automatic detection of abnormal ADs regions in mammograms using computer algorithms at initial stages could help radiologists and doctors. The architectural distortion star shapes ROIs detection, noise removal, and object location, affecting the classification p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…All the images are split into 7:3 and 5:5 to be the training set and the testing set, respectively. This split percentage was considered based on a review of the relevant literature [ 22 , 23 , 24 , 25 ]. In the positive cases, the lesions included calcifications, well-defined or localized masses, radially shaped masses, other and uncertain defined masses, structural distortions, and asymmetry tissue.…”
Section: Methodsmentioning
confidence: 99%
“…All the images are split into 7:3 and 5:5 to be the training set and the testing set, respectively. This split percentage was considered based on a review of the relevant literature [ 22 , 23 , 24 , 25 ]. In the positive cases, the lesions included calcifications, well-defined or localized masses, radially shaped masses, other and uncertain defined masses, structural distortions, and asymmetry tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Radiomics with machine learning, and deep learning using convolutional neural network (CNN), have been applied to analyze images for detection and diagnosis of lesions in various clinical applications (25-27). Several studies have applied AI for the detection of architectural distortion (13,28,29). Rehman et al proposed an automated computer-aided diagnostic system using computer vision and deep learning to predict breast cancer based on the architectural distortion on DM (13).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have applied AI for the detection of architectural distortion (13,28,29). Rehman et al proposed an automated computer-aided diagnostic system using computer vision and deep learning to predict breast cancer based on the architectural distortion on DM (13). Bahl et al performed a retrospective review and concluded that the presence of architectural distortion on mammography indicated malignancy in approximately 75% of cases (30).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations